2019
DOI: 10.1016/j.soilbio.2019.107577
|View full text |Cite
|
Sign up to set email alerts
|

Reduced soil respiration beneath invasive Rhododendron ponticum persists after cutting and is related to substrate quality rather than microbial community

Abstract: Reduced soil respiration beneath invasive Rhododendron ponticum persists after cutting and is related to substrate quality rather than microbial community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 66 publications
3
4
0
Order By: Relevance
“…Further, effects of removal treatments on bacterial and fungal community composition at the ASV level were subtle (P < 0.1) and only evident for the canopy plus forest floor removal treatment. These results are similar to a R. ponticum removal experiment in the UK, which reported no changes in microbial community structure (Jones et al, 2019), but contrast with a prior study from these same soils, which showed significant increases in microbial biomass and activities of microbial extracellular enzymes following R. maximum removal (Osburn et al, 2018). Together, these results suggest that R. maximum removal in the southern Appalachians is more likely to influence soil microbial activity than soil microbial community structure, at least in the short term.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Further, effects of removal treatments on bacterial and fungal community composition at the ASV level were subtle (P < 0.1) and only evident for the canopy plus forest floor removal treatment. These results are similar to a R. ponticum removal experiment in the UK, which reported no changes in microbial community structure (Jones et al, 2019), but contrast with a prior study from these same soils, which showed significant increases in microbial biomass and activities of microbial extracellular enzymes following R. maximum removal (Osburn et al, 2018). Together, these results suggest that R. maximum removal in the southern Appalachians is more likely to influence soil microbial activity than soil microbial community structure, at least in the short term.…”
Section: Discussionsupporting
confidence: 87%
“…In contrast, a prior experimental R. maximum subcanopy removal in the southern Appalachians revealed no evident effects on soil biota, including no changes in microbial biomass or invertebrate communities (Wright and Coleman, 2002), though that prior study was not replicated and was confounded by a hurricane that extensively disturbed the reference plot. Additionally, experimental removal of R. ponticum in the UK revealed no effects of canopy removal on microbial community structure (Jones et al, 2019). Together, these studies suggest that forest understory removal in general can influence soil microorganisms, but that R. maximum canopy removal alone may not be sufficient to alter soil bacterial and fungal communities.…”
Section: Introductionmentioning
confidence: 81%
“…Comparing to this study, no signi cant variations of SR due to narrow variation range of the ST was also detected in the tropical lowland rainforest of China during the spring season by Cui et al (2020) when the variations of ST were very less as we observed in the autumn season. The compatible trend of SR and ST with signi cant exponential relation of this study was most likely noticed previously while observing the cutting effect on SR in Rhododendron forest in the National Park area in the UK (Jones et al 2019). The result hence revealed that the factor for determining SR might be primarily the ST in the temperate forest, however, the angle of possession could be altered in different ecosystems (Dhital et The SWC dependency of SR of this R. arboretum forest was not satis ed to de ne the effect and variations of SR under different soil moisture conditions (Fig.…”
Section: Discussionsupporting
confidence: 87%
“…Similar to this study, Cui et al [43] has also detected no signifcant variations of SR due to narrow variation range of the ST in the tropical lowland rainforest of China during the spring season [43] when the variations of ST were very less as we observed in the autumn season. Te compatible trend of SR and ST with signifcant exponential relation of this study was most likely noticed previously while observing the cutting efect on SR in Rhododendron forest in the National Park area in the UK [44]. Te result hence revealed that the factor for determining SR might be primarily the ST in the temperate forest, however, the angle of possession could be altered in diferent ecosystems [34,45] and the exponential efect of ST on SR was the most quoted one [4,14,46].…”
Section: Discussionsupporting
confidence: 80%